ANALISIS PENGGUNAAN SUPERCONDUCTING FAULT CURRENT LIMITER (SFCL)PADA SISTEM DISTRIBUSI UNTUK MEREDUKSI ARUS HUBUNG SINGKAT DANMEMPERBAIKI TEGANGAN KEDIP (Jurnal Mahasiswa TEUB, 2024)
Berbek Feeder is one of the electricity distribution facilities of PLN UP3 Surabaya Selatan for consumers. In the distribution of electricity, Berbek Feeder often experiences short-circuit currents and voltage dips, which can degrade the quality of the  electric power. To protect equipment and improve the electrical system at the Gardu Induk Rungkut, a Superconducting Fault Current Limiter (SFCL) was installed at disturbance points of 25%, 50%, 75%, and 100%. This study aims to determine the short-circuit current disturbance values using ETAP 20.6 software by designing a single line diagram, entering data from PLN, and then conducting short-circuit simulations. The results showed that SFCL could reduce short-circuit currents: in three-phase disturbances, the current reduced by 0,98% from 512 to 606 kA within ½ cycle; in two-phase disturbances, the current reduced by 0,98% from 306 kA to 303 kA; and in single-phase-to-ground disturbances, the current reduced by 19,72% from 289 kA to 232 kA. SFCL also improved voltage dips in two-phase and single-phase-to-ground disturbances but not in three-phase disturbances due to the reactor impedance not being large enough to correct the voltage values. Keywords: Superconducting Fault Current Limiter (SFCL), short-circuit current, voltage sags, distribution system